2009
DOI: 10.1038/mt.2009.48
|View full text |Cite
|
Sign up to set email alerts
|

Regulated and Multiple miRNA and siRNA Delivery Into Primary Cells by a Lentiviral Platform

Abstract: RNA interference (RNAi) has tremendous potential for investigating gene function and developing new therapies. However, the design and validation of proficient vehicles for stable and safe microRNA (miR) and small interfering RNA (siRNA) delivery into relevant target cells remains an active area of investigation. Here, we developed a lentiviral platform to efficiently coexpress one or more natural/artificial miR together with a gene of interest from constitutive or regulated polymerase-II (Pol-II) promoters. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 51 publications
4
77
1
Order By: Relevance
“…In line with a previous report, 25 only miRNA expression from the intron maintained fluorescence intensity of the reporter, supposedly due to maintenance of the 5 0 cap as well as of the 3 0 poly(A) tail of the parental transcript (Figures 7B and 7C). In this context, the discovery of miR-126 as a potent HOXA9 cell expanding miRNA was unexpected, due to the presence of a miR-126 target site within the Hoxa9 homeodomain, and a previous report of miR-126 overexpression reducing HOXA9 cell colony forming potential as well as growth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with a previous report, 25 only miRNA expression from the intron maintained fluorescence intensity of the reporter, supposedly due to maintenance of the 5 0 cap as well as of the 3 0 poly(A) tail of the parental transcript (Figures 7B and 7C). In this context, the discovery of miR-126 as a potent HOXA9 cell expanding miRNA was unexpected, due to the presence of a miR-126 target site within the Hoxa9 homeodomain, and a previous report of miR-126 overexpression reducing HOXA9 cell colony forming potential as well as growth.…”
Section: Discussionsupporting
confidence: 93%
“…Since micro RNAs (miRNAs) play pivotal roles for cell homeostasis; e.g., proliferation, differentiation, and apoptosis, we first compared two miRNA overexpression strategies for their FGB-BC dependent multiplexing compatibility. 25 This showed that miRNA expression from the 3 0 UTR of the fluorescent marker reduced its MFI by 80%-90%, whereas miRNA expression from a 5 0 elongation factor 1a (EF1a)-derived intron maintained expression intensity in comparison to the parental FGB-BC vector design ( Figures 7A and 7B). This effect seemed largely miRNA independent since only one (miR-223) out of nine miRNAs with functional implications in hematopoiesis decreased the MFI of the respective color code (Figures 7C and 7D).…”
Section: Fgb-based Multiplexing Of Micrornas Identifies Mir-126 As Amentioning
confidence: 95%
“…The ShRNA sequence targeting the Hmgb1 gene was cloned into integrating lentiviral backbone pCCLsin.PPT.SFFV.EF Intron.mO2.Wpre. 37 This vector co-expresses the HMGB1 a-miR and the reporter transgene mOrange from the Spleen Focus Forming Virus promoter. The sequence of the siRNA used to generate the HMGB1 a-miR is: 5 0 -CAATATCCTTCTCATACTTCT-3 0 .…”
Section: Adenocarcinoma Cell Lines and Genetic Manipulationmentioning
confidence: 99%
“…As a specificity control for the Hmgb1 knockdown experiment, we used a lentiviral vector expressing an a-miR targeting LacZ. 37 VSV-G pseudotyped third generation lentiviral vectors expressing the amiRs were produced by transient four plasmid cotransfection into HEK293T cells and concentrated by ultracentrifugation. 38 Tumor cells were transduced with increasing multiplicity of infection (MOI) of the Hmgb1 or the LacZ a-miR LV.…”
Section: Adenocarcinoma Cell Lines and Genetic Manipulationmentioning
confidence: 99%
“…The most common design for these vectors has been to use strong RNA polymerase III (PolIII) promoters to drive the expression of short hairpin RNA (shRNA) where the interfering RNA is expressed as a stem loop structure that mimics the precursor microRNA (pre-miRNA) [5][6][7][8]. Most recently, several groups have gone a step further to mimic natural miRNA biology by producing artificial constructs that are analogous to the primary miRNA (pri-miRNA) [9][10][11][12]. These artificial miRNAs (amiRs) can be transcribed by RNA PolII promoters, as are most natural miRNAs.…”
Section: Introductionmentioning
confidence: 99%